2018
DOI: 10.1021/acs.jchemed.8b00455
|View full text |Cite
|
Sign up to set email alerts
|

Using Potentiometric Electrodes Based on Nonselective Polymeric Membranes as Potential Universal Detectors for Ion Chromatography: Investigating an Original Research Problem from an Inquiry-Based-Learning Perspective

Abstract: Because traditional laboratory practices in advanced chemistry education are being replaced by inquirybased approaches, we present herein a new laboratory activity based on a small research project that was designed and executed by students. The laboratory project aims at answering a well-defined research question: how far can potentiometric electrodes based on nonselective polymeric membranes be used as universal detectors in ion chromatography (IC)? Hence, the experiments were designed and conducted to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The LIG electrodes were fabricated by a one-step process of lasing a polyimide sheet (0.125 mm thick) with a CO 2 laser (see the Experimental Section and Figure 1). Such CO 2 lasers produce infrared light that heats polyimide and converts sp 3 hybridized carbon into sp 2 -hybridized carbon, thus converting polyimide to graphene. [27] Lasing parameters (speed, power, and frequency) were tuned to obtain graphene while preventing charring or burning of the polyimide, which can create a less conductive amorphous carbon structure.…”
Section: Lig Electrode Fabrication and Biofunctionalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The LIG electrodes were fabricated by a one-step process of lasing a polyimide sheet (0.125 mm thick) with a CO 2 laser (see the Experimental Section and Figure 1). Such CO 2 lasers produce infrared light that heats polyimide and converts sp 3 hybridized carbon into sp 2 -hybridized carbon, thus converting polyimide to graphene. [27] Lasing parameters (speed, power, and frequency) were tuned to obtain graphene while preventing charring or burning of the polyimide, which can create a less conductive amorphous carbon structure.…”
Section: Lig Electrode Fabrication and Biofunctionalizationmentioning
confidence: 99%
“…Solid‐state ISEs contain no filling solution between the ion‐selective membrane and the underlying electrode, and consequently do not exhibit the issues associated with ionic solution loss. Such ISEs have therefore been implemented in a wide variety of applications including in situ water quality analysis, [ 3 ] electrolyte sensing in sweat, [ 4 ] and fertilizer monitoring in soils. [ 5 ] However, solid‐state ISEs are often prone to large signal drift, which may be caused by the formation of an aqueous layer between the ion‐selective membrane and the electrode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between this potential and that provided by the reference electrode leads to the potentiometric readout, i.e., EMF of the electrochemical cell (Figure 1a). Besides this, the concentration dependence of the potentiometric signal with the activity of the primary ion is described by the Nernst equation, and the plot of the EMF versus logarithmic activity provides per se the calibration graph of the ISE (Figure 1b) [3], which is employed to detect unknown ion concentrations in (aqueous) samples.…”
Section: Introductionmentioning
confidence: 99%
“…Inquiry-based practices are emerging as an alternative approach to conventional pedagogical methods to teach laboratory practice. [25][26][27][28] As a matter of fact, it has been demonstrated that inquiry-based learning with platforms such as RoboGen offers great opportunities to teach multidisciplinary skills. 29,30 NMRviewers designed with Matlab have been introduced to promote complex data analyses and modeling, 31 and 3D printing has recently been introduced to classrooms to prepare intuitive visualizations of the physical and chemical properties of the elements in the periodic table.…”
Section: Introductionmentioning
confidence: 99%